Factors Affecting Capital Adequacy in the Ownership of Government Banks and Private Banks in Indonesia - Nirma Febyanti; Zulfikar Zulfikar (Cakrawala Repositori IMWI, 2023)
The Capital Adequacy Ratio (CAR) is a critical gauge for the sustainability of bank security. This study aims to identify the variables that influence capital adequacy. The banking sector listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021 served as the study's sample. Independent variables are profitability, non-performing loans, loan-to-deposit ratio, bank size and ownership. The dependent variable is CAR. The sampling technique used in this study was purposive sampling. The sample that met the criteria was 25 conventional banks consisting of 6 government-owned banks and 19 privately owned banks. The analysis method used is multiple regression analysis. The results of this study show that profitability, non-perfoming loans, bank size have a significant effect on CAR. Meanwhile, the loan to deposit ratio and ownership do not affect the CAR. This study's contribution to the management of the banking sector and regulators (Bank Indonesia) is that raising CAR is essential for boosting the competitiveness of the country's banking system.